2013
DOI: 10.1186/1471-2369-14-271
|View full text |Cite
|
Sign up to set email alerts
|

The use of absolute values improves performance of estimation formulae: a retrospective cross sectional study

Abstract: BackgroundEstimation of Glomerular Filtration Rate (GFR) by equations such as Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) or Modification of Diet in Renal Disease (MDRD) is usually expressed as a Body Surface Area (BSA) indexed value (ml/min per 1.73 m2). This can have severe clinical consequences in patients with extreme body sizes, resulting in an underestimation in the case of obesity or an overestimation of GFR in the case of underweight patients. The aim of this study was to compare the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
5
26
0
Order By: Relevance
“…36 The non-normalized CKD-EPI (mL/min) provided results, which were less biassed and comparable at predicting GFR (mL/min) at higher levels of GFR and body mass index. 37,38 A possible explanation for these findings would be that in this and the previously mentioned studies, the mean BSA for the sample was about 2 m 2 . 38 The BSA of 1.73 m 2 is the average normal mean value for young adults.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…36 The non-normalized CKD-EPI (mL/min) provided results, which were less biassed and comparable at predicting GFR (mL/min) at higher levels of GFR and body mass index. 37,38 A possible explanation for these findings would be that in this and the previously mentioned studies, the mean BSA for the sample was about 2 m 2 . 38 The BSA of 1.73 m 2 is the average normal mean value for young adults.…”
Section: Discussionsupporting
confidence: 51%
“…Using the GFR (mL/min) as the reference for dosing, the CKD‐EPI with the removal of BSA normalization (mL/min) was associated with greater dosing concordance of carboplatin . The non‐normalized CKD‐EPI (mL/min) provided results, which were less biassed and comparable at predicting GFR (mL/min) at higher levels of GFR and body mass index …”
Section: Discussionmentioning
confidence: 99%
“…This is not necessarily true because obesity-associated increases in BSA may not be matched to increased creatinine generation. We hence examined the impact of both absolute GFR and the CG-LBW equation in our study [25]. LBW has emerged as the most accurate adjustment for total weight 435 436 437 438 439 440 441 442 443 444 445 446 447 448 449 450 451 452 453 454 455 456 457 458 459 460 461 462 463 464 465 466 467 468 469 470 471 472 473 474 475 476 477 478 479 480 481 482 483 484 485 486 487 488 489 490 491 492 493 494 495 496 497 498 499 500 501 502 503 504 505 506 507 508 509 510 511 512 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 540 541 542 543 544 [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…Redal‐Baigorri et al . reported that removal of BSA normalisation with the CKD‐EPI equation (mL/min) was less biased than using the CKD‐EPI equation (mL/min/1.73 m 2 ) in predicting GFR (mL/min) measured using Cr‐EDTA, but did not report any comparative statistics regarding the performance of the CKD‐EPI equation with and without BSA normalisation. Lemoine et al .…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of the CKD-EPI_noBSA over the CKD-EPI equation has similarly been shown in the prediction of gentamicin clearances. 23,24 Redal-Baigorri et al reported that removal of BSA normalisation with the CKD-EPI equation (mL/min) was less biased than using the CKD-EPI equation (mL/min/ 1.73 m 2 ) in predicting GFR (mL/min) measured using Cr-EDTA, 25 but did not report any comparative statistics regarding the performance of the CKD-EPI equation with and without BSA normalisation. Lemoine et al reported from their study comprising obese patients, that CKD-EPI equation (mL/min/1.73 m 2 ) had less bias in the prediction of measured GFR (mL/min) than in the prediction of measured GFR normalised for BSA (mL/min/1.73 m 2 ).…”
Section: Discussionmentioning
confidence: 99%